Penggunaan e-book Multimodal Dalam Pembelajaran Bahasa Indonesia - Wahyuni, Dwita (STKIP ROKANIA, 2023)
The background of this research is the lack of knowledge and motivation of students in learning. For this reason, researcher used a multimodal ebook to increase students' knowledge and motivation in learning bahasa Indonseia. This research aims to determine the effectiveness of multimodal ebook used in learning bahasa Indonesia. The method used in this research is descriptive qualitative. The sample of this research is 77 students of Islamic Family Law Study Program Semester 1. The instruments used in this research were knowledge tests and questionnaires. The results of knowledge test showed that students' knowledge of the material after reading multimodal ebook was categorized as very good with an average of 85. Meanwhile, based on the questionnaires distributed, students responded very well to the use of multimodal ebook in learning bahasa Indonesia. The results of research showed that multimodal ebook were able to increase students' knowledge and motivation in learning bahasa Indonesia.